Anna Gamberini, Ceramiche fini ellenistiche da Phoinike Forme, produzioni, commerce - De Mitri, Carlo (Journal of Hellenistic Pottery and Material Culture, 2017)
This book represents the conclusion to a study project completed by Anna Gamberini concerning the ›Hellenistic Fine Ware‹ (ceramica ﬁne) discovered in Phoenike and studied over the last few years.